Case report: Polyarteritis nodosa as a substrate for a massive myocardial infarction - Solis-Jimenez, Fabio; Gonzalez-Ortiz, Araceli; Larios-Lara, Juan H.; Castro-Garcia, Carlos A.; Arteaga-Chan, Eduardo I.; Velazquez-Sanchez, Fernando; Vargas-Estrada, Jorge L.; Ramirez-Marcano, Erika Y.; Garaygordobil, Diego Araiza; Briseño De La Cruz, Jose L.; Gopar-Nieto, Rodrigo; Martinez, Daniel Sierra-Lara; et al. (Frontiers in Cardiovascular Medicine, 2023)
This report describes a rare case of a global myocardial infarction caused by severe vasospasm of the coronary arteries secondary to the administration of pyridostigmine in a patient with polyarteritis nodosa (PAN). Details about the clinical presentation, the typical electrocardiographic pattern of multivessel disease, the differential diagnoses suspected in the multi-imaging approach, and the treatment of cardiogenic shock are described. The definitive diagnosis of infarction and the histopathological findings compatible with polyarteritis nodosa were made by autopsy.